Dokar Dalam Pengembangan Pariwisata Di Pusat Kota Denpasar - Suarmana, I Wayan Restu (CV. ITTC INDONESIA, 2025)
Dokar is a traditional of transportation that is very unique. This traditional transportation uses animal power, namely horses, buffaloes and cows as the driving force. As time goes by, there are fewer and fewer dokars, this is because modern modes of transportation are increasingly developing, for example cars and motorbikes. In fact, if this traditional transportation is promoted and utilized well, it will have a very positive impact, especially from an economic perspective. The research method used is qualitative, this research method is based on the philosophy of postpositivism, used for research in natural object conditions, where the researcher is the key instrument, then sampling and data sources are carried out purposively and snowballing, then the data collection technique is carried out by triangulation (combined), data analysis is qualitative. The city of Denpasar initiated the medokaran, which is included in the city's cultural heritage tourism program. Medokaran program is aimed at introducing the potential of Denpasar City as a Heritage City. So this program uses dokar as a means of transportation to visit the Heritage City attraction in Denpasar City.